2018
DOI: 10.1007/s41669-018-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost Comparison of Single-Use Versus Reusable Bronchoscopes Used for Percutaneous Dilatational Tracheostomy

Abstract: We conclude that significant savings can be made by using single-use bronchoscopes to guide PDT in preference to reusable bronchoscopes. Results depend on hospital setting, the reprocessing procedures, annual bronchoscope procedures, individual repair cost, and repair rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…For reusable bronchoscopes, the costs per bronchoscopy decreased with a higher number of interventions. In contrast, a recent meta-analysis on cost effectiveness of single-use versus reusable bronchoscopes for PDT claimed single-use devices more cost effective [ 23 ], but disinfection costs in this analysis were far higher than in our institution and the main savings were achieved when additional expenses for the treatment of pneumonia due to the risk of cross-contamination, i.e. insufficient disinfection and spread of pathogens from one to the next patient, were included.…”
Section: Discussionmentioning
confidence: 71%
“…For reusable bronchoscopes, the costs per bronchoscopy decreased with a higher number of interventions. In contrast, a recent meta-analysis on cost effectiveness of single-use versus reusable bronchoscopes for PDT claimed single-use devices more cost effective [ 23 ], but disinfection costs in this analysis were far higher than in our institution and the main savings were achieved when additional expenses for the treatment of pneumonia due to the risk of cross-contamination, i.e. insufficient disinfection and spread of pathogens from one to the next patient, were included.…”
Section: Discussionmentioning
confidence: 71%
“…In that review, neither included the repair cost of RFBs nor performed a statistical analysis as performed in this meta-analysis. The authors assessed the repair cost via a survey and found that the percutaneous dilatory tracheostomy procedure cost was higher than the procedure cost for intubation [ 44 ]. It makes it impossible to know whether the cost difference between RFBs and SFBs was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…mask [ 72 ], utilising 3D printing [ 73 ] and reusable device, e.g. bronchoscopes, [ 74 ]. Liao et al.…”
Section: Future Ppe and Environmentally Sustainable Measuresmentioning
confidence: 99%